Needs Analysis for Developing STEM-PjBL-SSI-Based e-LKPD on Renewable Energy Using Oil Palm Empty Fruit Bunch Waste Context - Ratna Yuningsih; Kartini Herlina; Undang Rosidin; M Setyorini (Universitas Pendidikan Mandalika, 2026)
Renewable energy learning in science education requires contextual teaching materials that connect scientific concepts with local environmental issues and future-oriented skills. However, current classroom practices still face limitations in integrating project-based learning, socio-scientific issues, and entrepreneurial-oriented activities into structured learning resources. This study aimed to analyze the needs for developing a STEM-PjBL-SSI-based electronic student worksheet (e-LKPD) on renewable energy using oil palm empty fruit bunch waste as a local biomass context. A descriptive quantitative approach was employed through a survey involving 29 science teacher respondents. The data were collected using a questionnaire and analyzed descriptively using percentages. The results showed that Problem-Based Learning was the most frequently used learning model, applied by 51.7% of respondents, followed by Project-Based Learning at 37.9%, Discovery Learning at 27.6%, and Inquiry-Based Learning at 10.3%. The most commonly used teaching methods were discussion at 62.1% and experiment at 58.6%, while lectures were still used by 34.5% of respondents. In terms of learning resources, teachers mostly used learning videos at 72.4%, the internet at 65.5%, reference books at 55.2%, modules at 48.3%, and student worksheets at 44.8%. The findings also revealed that 62.1% of teachers were familiar with Socio-Scientific Issues, while misconceptions regarding renewable energy sources were still found among some respondents. Although 75.9% of teachers developed their own student worksheets, the existing worksheets had not systematically integrated STEM, project-based activities, socio-scientific issues, and entrepreneurial skill development. Therefore, the development of STEM-PjBL-SSI-based e-LKPD using oil palm empty fruit bunch waste as a renewable energy context is needed to support more contextual, interactive, and skill-oriented science learning.